Six Questions on the Greek Crisis that Are Difficult to Answer: Шест прашања за грчката криза што се тешки за одговарање - Alavanos, Alekos; Šišovski, Jordan (Identities: Journal for Politics, Gender and Culture, 2016)
Author(s): Alekos Alavanos | Алекос Алаванос Title (English): Six Questions on the Greek Crisis that Are Difficult to Answer Title (Macedonian): Шест прашања за грчката криза што се тешки за одговарање Translated by (English to Macedonian): Jordan Šišoski | Јордан Шишоски Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 12, No. 1-2 (Winter 2015 - Summer 2016) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 22-35 Page Count: 13 Citation (English): Alekos Alavanos, “Six Questions on the Greek Crisis that Are Difficult to Answer,” Identities: Journal for Politics, Gender and Culture, Vol. 12, No. 1-2 (Winter 2015 - Summer 2016): 22-35. Citation (Macedonian): Алекос Алаванос, „Шест прашања за грчката криза што се тешки за одговарање“, превод од англиски Јордан Шишоски, Идентитети: списание за политика, род и култура, т. 12, бр. 1-2 (зима 2015 - лето 2016): 22-35.